An overview of adverse event (AE) management for patients (pts) receiving abemaciclib. Issue 28 (1st October 2022) - Rugo, Hope S.; Vitko, Alexandra; Thoele, Kelli
Abstract : 239 Background: Abemaciclib is a selective cyclin-dependent kinase 4 & 6 inhibitor, approved for hormone receptor-positive (HR+), HER2- advanced breast cancer (aBC) as monotherapy or in combination with fulvestrant or nonsteroidal aromatase inhibitors. Abemaciclib is also approved in combination with endocrine therapy for the adjuvant treatment of HR+, HER2-, node-positive, high risk early BC (EBC). Despite demonstrated efficacy and overall tolerable safety profile, some pts discontinue abemaciclib without a prior dose reduction, highlighting the need for appropriate symptom management. This analysis aims to provide guidance on management of AEs for pts with aBC or EBC receiving abemaciclib. Methods: Study level data were collected for publications related to MONARCH 1, 2, and 3, and monarchE clinical trials. Endpoints included incidence of any-grade AEs, dose modifications, and discontinuations. Data on monitoring of AEs were also extracted. Results are presented descriptively. Results: Highest any-grade incidence of abemaciclib-associated AEs across trials include diarrhea (82-90%), fatigue (41-65%), nausea (30-64%) and neutropenia (37-50%). Notable AEs leading to dose reduction, omission and discontinuation were: diarrhea (14-21%; 15-24%; 1-5%), neutropenia (8-13%; 16-17%; 1-3%), and fatigue (5%; 5%; 2%) respectively. In the monarchE trial, discontinuations due to AEs were highest in the first month and stabilized after 6 months. AE monitoring and management are presented in Table. Conclusions: Appropriate AE monitoring, symptom management strategies, and patient counseling should be used to manage AEs with a goal to impact early discontinuation of abemaciclib.AE monitoring and dose modifications for pts receiving abemaciclib. Assessment Baseline Month 1/2 Month 3/4 Month 5 and beyond Week 1 2 3 4 Complete blood count and liver function tests * X X X Monthly As clinically indicated Diarrhea Instruct pts at the first sign of loose stools to initiate antidiarrheal therapy (such as loperamide), increase oral fluids, and notify their healthcare provider. Interstitial lung disease (ILD)/ pneumonitis Monitor for clinical symptoms or radiological changes indicative of ILD/pneumonitis. Consider steroids and/or antibiotics as treatment. For Grade ≥3, discontinue abemaciclib Venous thromboembolism Monitor pts for signs and symptoms of thrombosis and pulmonary embolism. and treat as medically appropriate. For Grade ≥3, suspend dose and treat as clinically indicated. Resume dose when pt is stable. Embryo-fetal toxicity Can cause fetal harm. Advise pts of potential risk to a fetus and to use effective contraception. Diarrhea, fatigue, and nausea For Grade ≥3, suspend dose until toxicity resolves to Grade ≤1 and resume at next lower dose. Neutropenia For Grade ≥3, suspend dose until toxicity resolves to Grade ≤2. Resume at next lower dose for recurrent Grade 3, and Grade 4. * ALT, AST and serum bilirubin.